2017
DOI: 10.1038/ncomms14046
|View full text |Cite
|
Sign up to set email alerts
|

Limiting parental feedback disrupts vocal development in marmoset monkeys

Abstract: Vocalizations of human infants undergo dramatic changes across the first year by becoming increasingly mature and speech-like. Human vocal development is partially dependent on learning by imitation through social feedback between infants and caregivers. Recent studies revealed similar developmental processes being influenced by parental feedback in marmoset monkeys for apparently innate vocalizations. Marmosets produce infant-specific vocalizations that disappear after the first postnatal months. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 65 publications
(111 reference statements)
3
105
0
Order By: Relevance
“…They can also convey identity through aspects of their calls [65]. Their calls change from infancy into adulthood, much like in humans, and limiting parent feedback disrupts this development [66]. Several Old World monkeys display relevant vocal learning abilities.…”
Section: Box 3 Evidence Of Vocal Learning Abilities In Species Outsimentioning
confidence: 99%
See 1 more Smart Citation
“…They can also convey identity through aspects of their calls [65]. Their calls change from infancy into adulthood, much like in humans, and limiting parent feedback disrupts this development [66]. Several Old World monkeys display relevant vocal learning abilities.…”
Section: Box 3 Evidence Of Vocal Learning Abilities In Species Outsimentioning
confidence: 99%
“…Taking all the evidence available into account, and placing the focus in the behavior observed, we believe a more accurate "vocal learners list" (albeit with some tentative cases) would be the one we sketch in Fig 1. We can see in this new list that it is possible to reduce the gap between us and the other vocal learners in a principled way. Although a direct forebrain-larynx connection is maybe not shared, there is much that is shared: similar patterns of early postnatal vocal development [66], volition [24], both voiceless and even voiced calls [42], socially reinforced vocal production, etc.…”
Section: Tree Of Vocal Learners With a Focus On Behaviormentioning
confidence: 99%
“…Recently, this perception has dramatically changed. Current studies have revealed distinct learning mechanisms during vocal development [6][7][8] and vocal flexibility, allowing monkeys to cognitively control when [9,10], where [11], and what to vocalize [10,12,13]. However, specific call features (e.g., duration, frequency) remain surprisingly robust and stable in adult monkeys, resulting in rather stereotyped and discrete call patterns [14].…”
Section: In Briefmentioning
confidence: 99%
“…The spectrograms were calculated using a 1024-point FFT window, Hanning window (512 samples), and 125-sample overlap. We classified marmoset vocalizations into groups using previous definitions [8,14,19,38]. Calls were manually classified as phee, twitter, tsik, and ekk calls based on their spectro-temporal profile and auditory playback.…”
Section: Acoustic Analysismentioning
confidence: 99%
“…The range of vocalizations is well-conserved in monkeys raised in captive colonies bred for research purposes and can be evaluated without complex elicitation protocols [e.g., 28, 29, 30, 31, 32]. Vocalizations develop in common marmosets with modeling from parental feedback [33, 34], and call acoustic parameters develop differently based on call type [31]. Most published evaluations of marmoset vocalization development are performed using specialized audio recording equipment, and call analysis requires specific training.…”
Section: Introductionmentioning
confidence: 99%